Bus transit capacity and level of service of NGV bus - Preetham, Guntha Rajeev; Kunnawee Kanitpong; Ampol Karoonsoontawong; Surachet Pravinvongvuth; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
The TU bus transit play a large role in the public transportation of both staff as well as students in the Thammasat university. The buses have different routes and different schedules according to the availability and usage of the passengers. Traffic congestion occurs when there are more songthaews, bike taxis and private cars in the Thammasat university which are the main problems to reduce the passengers in the buses. Due to this, the usage of TU buses is decreasing day by day. in some cases, people wait for the bus but songthaews come and board the passengers. passengers wait a lot of time for the arrival of buses due to poor scheduling of bus timings and traffic congestion. in this study the bus stop capacity and level of service of TU transit are calculated. Moreover, the final results from this research study would like to suggest the usage of buses at particular stop per hour at peak intervals of time, the alighting and boarding rates of the passengers and finally to calculate the level of service of TU bus transit of the least critical bus stop capacity value as it determines the bus transit capacity. The Recommendations for improvement of the bus stop capacity were organized with similarity between each Recommendation calculation.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Science in Transportation Engineering
Research Studies Project Report (M.Sci.) - Asian Institute of Technology, 2020
Keywords: Buses -- Thailand -- Thammasat University; Bus lines -- Thailand -- Thammasat University; Shuttle services -- Thailand -- Thammasat University